PENGGUNAAN MASKER UNTUK BUDAYA HIDUP SEHAT YANG BARU PADA MASA PANDEMI COVID-19 - Ria Karina; Natalis Christian; Iskandar Itan; Reymon Yulianto; Arya Dita; Cindy Tan; Elbert Henokh Tanberius; Fiqri Pramanda; Karyn Karyn; Melisa Melisa; Yehezkiel Putra Galang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Covid-19's global pandemic has caused chaos in various countries of the world. One of those affected by the pandemic is Indonesia. The health sector, economic sector, and security sector could be threatened in the current global pandemic. The need for people to get used to a healthy lifestyle is now very important. The purpose of this activity is to help the community independently make masks to be useful to protect themselves, especially during this pandemic. Masks have become an important daily need for daily use. In addition, with the increasing need for masks, mask prices have also increased and decreased mask availability especially during the initial pandemic period. This activity is designed to provide education in the form of a cloth mask-making tutorial to the public through webinars and social media such as YouTube that can be accessed.